The effect of motion patterns on edge-loading of metal-on-metal hip resurfacing. - Mellon, S; Kwon, Y; Glyn-Jones, S; Murray, D; Gill, H (2011)
The occurrence of pseudotumours (soft tissue masses relating to the hip joint) following metal-on-metal hip resurfacing arthroplasty (MoMHRA) has been associated with high serum metal ion levels and consequently higher than normal bearing wear. We investigated the relationship between serum metal ion levels and contact stress on the acetabular component of MoMHRA patients for two functional activities; gait and stair descent. Four subjects with MoMHRA, who had their serum metal ion levels measured, underwent motion analysis followed by CT scanning. Their motion capture data was combined with published hip contact forces and finite element models representing 14% (peak force) and 60% (end of stance) of the gait cycle and 52% (peak force) of stair descent activity were created. The inclination angle of the acetabular component was increased by 10° in 1° intervals and the contact stresses were determined at each interval for each subject. When the inclination angle was altered in such a way as to cause the hip contact force to pass through the edge of the acetabular component edge-loading occurred. Edge-loading increased the contact stress by at least 50%; the maximum increase was 108%. Patients with low serum metal ion levels showed no increase in contact stress at peak force during gait or stair descent. Patients with high serum metal ion levels exhibited edge-loading with an increase to the inclination angle of their acetabular components. The increase in inclination angle that induced edge-loading for these subjects was less than the inter-subject variability in the angle of published hip contact forces. The results of this study suggest that high serum metal ion levels are the result of inclination angle influenced edge-loading but that edge-loading cannot be attributed to inclination angle alone and that an individual's activity patterns can reduce or even override the influence of a steep acetabular component and prevent edge-loading.